PEMBERDAYAAN EKONOMI RUMAH TANGGA KELOMPOK WANITA TANI KEMIRI EDUM DENGAN OLAHAN SALAK SARISA MERAPI DI DESA PURWOBINANGUN KECAMATAN PAKEM KABUPATEN SLEMAN - Faishol Jundi Abaidah; Wahyu Setya Ratri; Artita Devi Maharani (JURNAL ILMIAH AGRITAS, 2026)
This study aims to describe the economic empowerment of the Women Farmers Group (KWT) Kemiri Edum in Purwobinangun Village, Sleman, and to identify its impact on group members using the Asset-Based Community Development (ABCD) approach. The research method used is a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The sample consisted of informants determined by a census, including the KWT leader, members, and agricultural extension officers. The empowerment process was analyzed based on the five stages of the ABCD approach, namely discovery (exploration of local assets in the form of salak pondoh and women’s social capital), dream (building a collective vision for increasing the added value of salak), design (preparation of institutional structures and division of labor), define (implementation of operational activities and regular evaluations), and destiny (continuity of production, product innovation, and external support from the government and financial institutions). The impact of empowerment is seen from the increase in members’ income, with an average of Rp.1,525,000 per month and SHU distribution of Rp.2,000,000 every before Eid. This condition also changes the family’s economic structure from previously relying only on the husband’s income to dual-income (husband and wife). This income helps fulfill household needs such as consumption, education, and health, while strengthening the family’s economic independence. In addition, the KWT institution developed into the KWT Madya category through the implementation of the five ABCD stages, active member participation, and broad partnerships, thereby strengthening the role of women in sustainable village economic development.